2014
DOI: 10.1021/jz500174x
|View full text |Cite
|
Sign up to set email alerts
|

Protein Thermal Conductivity Measured in the Solid State Reveals Anharmonic Interactions of Vibrations in a Fractal Structure

Abstract: Energy processes and vibrations in biological macromolecules such as proteins ultimately dictate biological, chemical, and physical functions in living materials. These energetic vibrations in the ribbon-like motifs of proteins interact on self-similar structures and fractal-like objects over a range of length scales of the protein (a few angstroms to the size of the protein itself, a few nanometers). In fact, the fractal geometries of protein molecules create a complex network of vibrations; therefore, protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 55 publications
5
30
0
Order By: Relevance
“…53 This approach has been adopted to calculate thermal transport coefficients of aperiodic mesoscopic systems, including proteins. 4 Results for the latter compare reasonably well over a sizable range of temperature with calculations that incorporate anharmonic effects, 54,55 though anharmonicity contributes significantly to thermal transport coefficients around 300 K. 56 An additional approximation can be made to estimate local energy diffusion within a mesoscopic object. Communication maps are based on calculating first the heat current operator in harmonic approximation, then FIG.…”
Section: Introductionmentioning
confidence: 65%
“…53 This approach has been adopted to calculate thermal transport coefficients of aperiodic mesoscopic systems, including proteins. 4 Results for the latter compare reasonably well over a sizable range of temperature with calculations that incorporate anharmonic effects, 54,55 though anharmonicity contributes significantly to thermal transport coefficients around 300 K. 56 An additional approximation can be made to estimate local energy diffusion within a mesoscopic object. Communication maps are based on calculating first the heat current operator in harmonic approximation, then FIG.…”
Section: Introductionmentioning
confidence: 65%
“…[35][36][37][38][39]41 The temperature trends of the thermal conductance per unit area of the F21PA molecule suggest that thermal vibrations are interacting anharmonically in the molecule, consistent with previous analyses of the thermal conductivity trends in amorphous materials with complex unit cells, polymers and solid proteins. [78][79][80] To the best of our knowledge, this is the first observation of diffusive scattering of thermal vibrations in an interface-modifying molecule.…”
Section: Introductionmentioning
confidence: 71%
“…This result suggests that the presence of proteins does not significantly change the value of ITC. Previous studies reported that hydrogen bonds between proteins and intercalated water molecules are responsible for a promotion of interfacial thermal transport, which explains the fact that the protein–water interface (with hydrogen bonds) has a higher ITC of 100–300 MW m −2 K −1 than that for the octane–water interface (without hydrogen bonds), that is, 65 MW m −2 K −1 (refs 24 , 25 , 26 , 27 , 28 ). In our model, however, this effect is negligible because of the limited contact between intercalated water layer and protein.…”
Section: Resultsmentioning
confidence: 99%